Statistical description of a non-Brownian suspension - Cichocki, B.; Sadlej, K. (Archives of Mechanics, 2006)
A suspension of non-Brownian particles in a constant, external force field is studied. Statistical description of the system, based on reduced distribution functions is found. A hierarchy of equations for the correlation functions, analogous to the BBGKY hierarchy known from the kinetic theory of gases, is derived and thoroughly analysed. As an example, the problem of deriving the two-particle correlation function for a sedimenting system is considered.